Suplementasi Hidrolisat Glukomanan Tepung Porang (Amorphophallus oncophillus) pada Produk Minuman Sinbiotik - Chandra Utami Wirawati; Dwi Eva Nirmagustina (Jurnal Penelitian Pertanian Terapan, 2022)
Synbiotics is a combination of prebiotics and probiotics that are believed to have a synergistic effect not only by inhibiting the growth of pathogenic bacteria and enhancing the growth of beneficial organisms, but also play a role as functional foods. This study was conducted to evaluate the konjac glucomannan hydrolyzate in synbiotics fermented milk. Factorial Randomized Block Design (RAK) was applied in this experiment. The combination of konjac glucomannan hydrolyzate (0%, 0.5%, 1%, 1.5%) and storage time (0 day, 30 days, 60 days) were applied to measure the acidity (pH), lactic acid konsentration and viscosity. Meanwhile viability of lactic acid bacteria and antibacterial activity were measure . The result showed that konjac glucomannan hydrolyzate supplementation were decreased product acidity (pH) and viscosity, but increased the lactic acid concentration during 60 days storage. Viability of lactic acid bacteria during 60 days storage were decreased except for 1% and 1.5% concentration. The synbiotic product showed antagonistic activity against pathogenic bacteria i.e. E. coli ATCC 25922, S. aureus ATCC 25923, and S. Typhimurium ATCC 14028. Supplementation of 1% glucomannan hydrolyzate for 60 days at 5oC showed the best characteristics in synbiotic product namely 3.45 acidity (pH), 1.24% total lactic acid , 3.24 Cp viscosity, and 8.69 log CFU/g total lactic acid bacteria.